Perceived Benefits of Online Shopping : Scale Modification and Validation - Tomar, Vivek Singh; Sharma, Ashok; Pandey, Neeraj (Indian Journal of Marketing, 2018)
Use of the Internet has opened countless business opportunities, and online shopping is one of the most popular among all. Benefit perception towards online shopping is one of the major influencing factors towards consumer’s online purchase decisions. Therefore, the current study aimed at exploration of the construct : perceived benefits of online shopping (PBOS). The study rigorously explored the past research studies though secondary literature review to develop the primary understanding of the construct, which was followed by modification of existing scales to propose a new scale to measure PBOS. Understanding of the construct PBOS through literature review was followed up through refinement, modification, and validation of a more relevant and contemporary scale to measure PBOS. The past and existing scales generally measured benefit and risk perception concurrently to capture the overall perception towards online shopping, while this study focused on measurement of PBOS independently to get a focused insight. A list of 39 items on PBOS from one of the past studies was further refined to get a modified scale with 21 items. These 21 items were further used in two distinctive studies with different samples of sizes 350 and 650 collected during separate time periods through independent studies. EFA followed by CFA in two independent studies resulted in the development of a comprehensive 21 item scale measuring seven dimensions of PBOS.